Un nouveau calendrier de saints égyptien (P. Iand. inv. 318) - Gascou, Jean (Analecta Bollandiana, 1989)
Papyrus Iandana inv. 318 previously published as a "Namenliste" (Aegyptus, 67 [1987], p. 69-70) is in fact a calendar of Coptic saints. Among other points of interest, it vindicates the accuracy of the entry of Synaxar, 5 amšîr, devoted to Saint Apollos.